New reaction development using N-hetereocyclic carbenes and phosphines as nucleophilic organocatalysts - Jin, Zhichao (2016)
This thesis focuses on exploring new reaction modes that enabled by nucleophilic organocatalysts including N-heterocyclic carbenes (NHCs) and organophosphines. It contains five parts: Chapter 1 gives brief introductions to the history and development of both NHC catalysis and organophosphine catalysis, and shows the future challenges in these fields. Chapter 2 describes a highly enantioselective cascade reaction that consisted of an NHC catalyzed N-S bond cleavage and the stereoselective Michael addition that induced by a thiourea-tertial amine based multifunctional cocatalyst. Substituted 3-tosylpropan-1-one could be obtained in up to 84% yield with up to >99:1 er value. This work represents the first example of NHC/thiourea/tertial amine co-catalysis. Chapter 3 is about the direct β-activation of aliphatic substituted carboxylic anhydride. We demonstrate the efficiency of this methodology through reactions of simple anhydrides with several nucleophiles. The product of (E)-((4R,5R)-4-methyl-2,5-diphenylcyclopent-2-en-1-ylidene)(phenyl)methyl butyrate and its analogues could be obtained in up to 75% yield with up to 99:1 er value as single diastereomers. The product of ((1R,5R)-5-methylcyclopent-3-ene-1,3-diyl)dibenzene and its analogues could be obtained in up to 95% yield in up to 98:2 er value and up to >20:1 dr value. The product of (2S,3S)-3-methyl-1'-trityl-3,4-dihydro-5H-spiro[furan-2,3'-indoline]-2',5-dione and its analogues could be obtained in up to 96% yield with up to >99:1 er value and up to 12:1 dr value. Chapter 4 introduces the one-pot cascade reactions of β-activation of the simplest propoinic carboxylic acid. We again showed the efficiency of this approach through reactions with various nucleophilic substrates. (S)-1'-trityl-3,4-dihydro-5H-spiro[furan-2,3'-indoline]-2',5-dione and its analogues could be obtained in up to 99% yield with up to 96:4 er. Benzhydryl (R)-5-oxo-2-phenyltetrahydrofuran-2-carboxylate and its analogues could be obtained in up to 99% yield with up to 96:4 er. We also showed the necessity of this methodology by comparing the acid activation approach with the anhydride approach using the same substrates under similar reaction conditions. Chapter 5 describes a novel [4+2] cycloaddition reaction catalyzed by organophosphines. This transformation could go through a highly enantio- and diastereo-selective manner by applying a multifunctional phosphine catalyst that derived from natural exsited amino acid. Corresponding product 2-phenyl-3-tosyl-4,4a-dihydro-3H-chromeno[3,4-c]pyridin-5(10bH)-one and its analogue could be obtained in up to 99% yield with up to >99:1 er value as single diastereomers.